The Artpreneurship: Innovate to Overcome the Challenge - Kusuma, Gabriella Hanny; Kurniawati, Anggreni Dian; Junaedi, Sheellyana, M. F.; Widiastuti, Theresia Diah (UI Scholars Hub, 2023)
This community engagement program aimed to improve the innovation of artpreneurs, a combination of artistic qualities with business sense in cultural sectors, overcoming the impact of the disruptive moment, such as the COVID-19 pandemic. This program used the Asset-Based Community Development method to explore the needs of the community. The exploration process used an appreciative inquiry approach to determine strengths, opportunities, aspirations, and results based on the inquiry from the community. This program was conducted in Ngestiharjo Village, Yogyakarta, Indonesia, as a part of the community service learning program Wiradesa conducted by the students and organized by Universitas Atma Jaya Yogyakarta. The participants were five artpreneurs who were members of the Ngestiharjo art community and own small and medium-sized enterprises. This community engagement program successfully defined the potential resources of the Ngestiharjo artpreneurs. The potential resources are intangible (network, cohesion, experiences, creativity, and quality) and tangible (venue and digital equipment) assets. These potential assets become an important element in developing a program using the Theory of Change (ToC). The results of this community engagement program are expressed in the ToC scheme which could be a guide for the members of the Ngestiharjo art community to improve their capacity to achieve their goals. Despite its limitations, this method of community development is replicable for communities with similar situations, striving toward innovations in maximizing arts and culture.